2021
DOI: 10.1136/ijgc-2021-003017
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3, randomized, open-label study of pembrolizumab plus lenvatinib versus chemotherapy for first-line treatment of advanced or recurrent endometrial cancer: ENGOT-en9/LEAP-001

Abstract: BackgroundPembrolizumab plus lenvatinib is a novel combination with promising efficacy in patients with advanced and recurrent endometrial cancer. This combination demonstrated high objective response rates in a single-arm phase 1b/2 trial of lenvatinib plus pembrolizumab in patients with advanced endometrial cancer (KEYNOTE-146/Study 111) after ≤2 previous lines of therapy. In a randomized phase 3 trial of lenvatinib in combination with pembrolizumab versus treatment of physician's choice in patients with adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…We were aware of the activity of immunotherapeutic agents (anti-programmed death-1 monoclonal antibody) either alone [ 62 ] or in combination with tyrosine kinase inhibitors in advanced EMC that had failed prior to systemic therapy [ 63 ]. The demonstrated efficacy of these agents in phase I/II studies led to phase III trials that had recently reported superior survival outcomes over standard chemotherapy with paclitaxel and carboplatin [ 64 ] or are still ongoing [ 65 ]. Whether these agents will be used in the future as neoadjuvant treatment in advanced and inoperable EMC is yet to be seen.…”
Section: Resultsmentioning
confidence: 99%
“…We were aware of the activity of immunotherapeutic agents (anti-programmed death-1 monoclonal antibody) either alone [ 62 ] or in combination with tyrosine kinase inhibitors in advanced EMC that had failed prior to systemic therapy [ 63 ]. The demonstrated efficacy of these agents in phase I/II studies led to phase III trials that had recently reported superior survival outcomes over standard chemotherapy with paclitaxel and carboplatin [ 64 ] or are still ongoing [ 65 ]. Whether these agents will be used in the future as neoadjuvant treatment in advanced and inoperable EMC is yet to be seen.…”
Section: Resultsmentioning
confidence: 99%
“…Lenvatinib combined anti-PD-1 has been approved in endometrial carcinoma and renal cell carcinoma. In KEYNOTE-775/Study 309, lenvatinib and pembrolizumab demonstrated an ORR of 30%, PFS 6.6 months (HR 0.60) and OS 17.4 months (HR 0.68), which was superior to doxorubicin or paclitaxel in platinum-experienced endometrial carcinoma [ 23 ]. In renal cell carcinoma, the combination of lenvatinib and pembrolizumab was highly effective with an ORR of 38% in the phase Ib/II trial KEYNOTE-146 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…More information on IHC including MMR proteins ( MLH1, MSH2, MSH6 , and PMS2 ) and p53 were shown in Supplementary Table 1 . Currently, two phase III RCTs are ongoing for newly diagnosed advanced or recurrent EC: the ENGOT-en9/LEAP-001 trial, comparing the efficacy and safety of pembrolizumab plus lenvatinib combination therapy vs. paclitaxel-carboplatin [ 23 ], and the ENGOT-en6/NSGO-RUBY trial, comparing the efficacy and safety of dostarlimab plus paclitaxel-carboplatin vs. placebo plus paclitaxel-carboplatin [ 24 ]. If these two trials commonly result in positive results from the experimental arms, incorporation of immune checkpoint inhibitors might further expand the use of NAC in the management of unresectable metastatic EC.…”
Section: Discussionmentioning
confidence: 99%